Readiness Analysis Accredity Documents Of Individual Health Efforts Work Group Karamat Phc District Buol In Facing Accreditation - Moh Yasin (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Accreditation PHC aims to improve the quality of services at the first level of health facilities especially PHC, but in reality Public health center has not been able to implement all the components expected, this is caused by several factors; Lack of understanding of Accreditation Instrument standards, lack of Human Resources and inadequate infrastructure. The purpose of this study is to explore or describe the Accreditation Readiness of the Work Group Individual Health Efforts Karamat Public Health Center in Facing accreditation. The design of this study is qualitative with a Case Study approach. The sampling technique used was purposive sampling with 9 informants. Triangulation was conducted on 3 source. Data collection techniques carried out by interview and triangulation of sources. Data Sources In this study are the Accreditation and Triangulation Sources Team. Data acquisition techniques: in-depth interviews and documentation. The results of the study showing that in general the Karamat Public Health Center in its efforts to prepare accreditation documents was guide book by the accreditation of the First Level Health Facilities and district level the Accreditation advisor Team.The findings found that the Karamat Public Health Center do not have dentists, laboratory analysts and staff who have dual duties and do not yet have a system of treating hazardous waste materials, medical waste or non-medical waste and the need for equipment in each room that is inadequate. From the completeness of documents by using the completeness check list. from 81 documents; 23 documents have been fulfilled, 29 documents have been fulfilled and 29 documents have not been fulfilled. an average of 20.8% is included in the partially met category. And according to the accreditation manual, the Karamat Public Health Center in particular the Individual Health Efforts Work Group is Worth for in Value. The efforts of the Karamat Public Health Center Accreditation Team in the efforts to fulfill the accreditation documents in addition to the mentoring method also make several of efforts including Training, Implementation of self-assessment, Discussion of the results of Self-assessment, Worksop and comparative study to Public Health Center which has been accredited outside the Central Selebes region